2016
DOI: 10.4103/1319-3767.182451
|View full text |Cite
|
Sign up to set email alerts
|

An open-label randomized control study to compare the efficacy of vitamin e versus ursodeoxycholic acid in nondiabetic and noncirrhotic Indian NAFLD patients

Abstract: Background/Aim:The study was carried out to compare the efficacy of Vitamin E versus Ursodeoxycholic acid (UDCA) in nondiabetic nonalcoholic fatty liver disease (NAFLD) patients.Patients and Methods:We randomized 250 non cirrhotic and non diabetic NAFLD patients diagnosed on ultrasound, with raised alanine aminotransferase (ALT) level. (>40 IU/L), to receive Vitamin E 400 mg twice a day (Group A) or UDCA 300 mg twice a day (Group B) for 52 weeks. Lifestyle modification to achieve at least 5% weight reduction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Several previous studies evaluated longitudinal changes in non‐invasive measures of fibrosis and associations with histologic or clinical outcomes; however, limited reports have paired these assessments with liver biopsy evaluations . Among the serum markers currently available for non‐invasive evaluation of fibrosis, APRI, FIB‐4 index and NFS have been used and validated most extensively .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies evaluated longitudinal changes in non‐invasive measures of fibrosis and associations with histologic or clinical outcomes; however, limited reports have paired these assessments with liver biopsy evaluations . Among the serum markers currently available for non‐invasive evaluation of fibrosis, APRI, FIB‐4 index and NFS have been used and validated most extensively .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the limited sampling frequency in the FLINT trial for both laboratory biomarkers (ie, once every 24 weeks) and histologic evaluations (ie, at baseline and 72 weeks) precluded the ability to assess the time to effect of OCA on these outcomes and the predictive value of APRI, FIB-4 index, and NFS at time points earlier than 24 weeks. Moreover, the relatively wide CIs for the AUROC findings in this analysis may suggest the need to investigate the predictive value of additional biomarkers.Several previous studies evaluated longitudinal changes in non-invasive measures of fibrosis and associations with histologic or clinical outcomes[24][25][26][27][28][29][30] ; however, limited reports have paired these assessments with liver biopsy evaluations 25,27,28,30. Among the serum markers currently available for non-invasive evaluation of fibrosis, APRI, FIB-4 index and NFS have been used and validated most extensively 9,31.…”
mentioning
confidence: 99%
“…However, multiple trials have shown a lack of improvement in NAFLD or NASH and it is not currently recommended for use in patients with NAFLD or NASH (Dufour et al, 2006; Haedrich and Dufour, 2011; Leuschner et al, 2010; Lindor et al, 2004; Parikh et al, 2016). C57BL/6 mice fed a HFD given UDCA in conjunction with omega-3 had decreased liver fibrosis and inflammation compared with a group of mice given only omega-3 (Kim et al, 2014).…”
Section: Current Therapiesmentioning
confidence: 99%
“…In a randomized controlled trial conducted by Parikh et al, patients with NAFLD were given either vitamin E or UDCA (Parikh et al, 2016). UDCA was not superior to vitamin E when comparing improvements in ALT and NAFLD fibrosis score.…”
Section: Current Therapiesmentioning
confidence: 99%
“…These include pentoxifylline, orlistat, Vitamin E, ursodeoxycholic acid, omega -3 fatty acids, and insulin sensitizers and lipid-lowering agents [6]. However, the American Association for the Study of Liver Diseases (AASLD) recommends the use of Vitamin E administered at daily doses of 800 IU/day in non-diabetic adults with biopsy-proven NASH and is considered as a first line pharmacotherapy for this patient population [7].…”
Section: Introductionmentioning
confidence: 99%